Insights into morphological evolution and cycling behaviour of lithium metal anode under mechanical pressure - Yin, Xuesong (2020)
Dendritic Li formation is one of the critical reasons for the failure of Li batteries. In order to improve the lithium metal anode performance, a better understanding of the growth mechanisms of Li dendrites is necessary. Due to the malleable nature of lithium metal, mechanical pressure should play an important role in determining the morphology and cycling behaviour of Li anode. Here we investigated the effect of an applied external pressure on the electrochemical deposition of lithium metal. Instead of a highly porous, wire-like Li growth in the absence of pressure, a much more compact Li deposition can be achieved when a pressure is applied to the batteries in the charge/discharge processes. The improved Li deposition/stripping behaviour in the pressed cells yields a 5% higher Coulombic efficiency (~90%) and more than 5-fold longer cycling life than the cells without pressure at a current density of 2 mA/cm2. The use of pressure in shaping Li metal is an effective approach to address the Li metal problem and advance Li technologies in the future.